Investigating a high ozone episode in a rural mountain site - Monteiro, A. (2012)
A very high ozone episode with observed hourly values above 350 mug m(-3) occurred in July 2005 at the Lamas d'Olo air quality monitoring station, located in a mountainous area in the north of Portugal. Aiming to identify the origin and formation of this ozone-rich episode, a statistical analysis and a modelling approach were applied. A cross-spectrum analysis in the frequency domain and a synoptic analysis of the meteorological and air quality time series were performed. In order to go further in this analysis, a numerical modelling approach was applied. The results indicate that the transport of ozone and its precursors is the main responsible for the high ozone concentrations. Together with the local mountain breeze and subsidence conditions, the sea-breeze circulation transporting pollutants from the coastal urban and industrialized areas that reach the site during late afternoon turn out to be the driving forces for the ozone peaks.